2015
DOI: 10.1007/s00508-015-0811-x
|View full text |Cite
|
Sign up to set email alerts
|

Needle fragment embolism into the right ventricle: a rare cause of chest pain case report and literature review

Abstract: Chest pain in young adults is usually self-limited and of benign etiology. However, rare causes of chest pain must be considered in patients for whom initial diagnostic tests are negative, particularly if unusual risk factors are identified. The authors present a rare case describing a 27-year-old male intravenous drug user who developed transient chest pain most likely secondary to pericardial irritation caused by a needle fragment that embolized from a peripheral vein to his right ventricle. The current lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In a retrospective study of 70 IVDUs conducted by Norfolk and Gray, 20% of the subjects reported a history of broken needle fragments during drug use [1]. Although there are multiple reports of needle embolization related to various etiologies, including acupuncture, self-inflicted injury, and trauma, needle fragment embolization to the heart in the IVDU population has rarely been reported [2,3]. After an extensive literature search, we found only 12 case reports describing cardiac embolization of needle fragments in IVDUs between 1988 and 2019 [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 70 IVDUs conducted by Norfolk and Gray, 20% of the subjects reported a history of broken needle fragments during drug use [1]. Although there are multiple reports of needle embolization related to various etiologies, including acupuncture, self-inflicted injury, and trauma, needle fragment embolization to the heart in the IVDU population has rarely been reported [2,3]. After an extensive literature search, we found only 12 case reports describing cardiac embolization of needle fragments in IVDUs between 1988 and 2019 [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…After an extensive literature search, we found 12 case reports describing cardiac embolization of needle fragments in IV drug users between 1988-2019. (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Characteristics of these case reports including chief complaint, cardiac complications and type of interventions performed are noted in Table 1. Considering the number of IV drug users and reported frequency of broken needle fragments by this population, the low number of case reports of needle embolization to the heart in this population is surprising.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Although there are multiple reports of needle embolization related to various etiologies including acupuncture, self-inflicted injury, trauma etc, needle fragment embolization to the heart in the IV drug user population has been rarely reported. (2,3). In this case report, we describe a case of needle embolism to the heart in a 28 year old IV drug user and review the existing literature on similar cases.…”
Section: Introductionmentioning
confidence: 97%
“…To our knowledge, only a few cases of needle embolization in pulmonary vasculature or inside the right heart are reported in the literature, most of them in drug abusers or after iatrogenic accidents [9][10][11][12][13][14][15].…”
Section: Case Presentationmentioning
confidence: 99%